Importin‐7 Mediates Nuclear Trafficking of DNA in Mammalian Cells. (7th November 2012) - Dhanoya, Arjun; Wang, Tse; Keshavarz‐Moore, Eli; Fassati, Ariberto; Chain, Benjamin M.
<x xml:space="preserve">Abstract</x> Eukaryotic cells have the ability to uptake and transport endogenous and exogenous DNA in their nuclei, however little is known about the specific pathways involved. Here we show that the nuclear transport receptor importin 7 (imp7) supports nuclear import of supercoiled plasmid DNA and human mitochondrial DNA in a Ran and energy‐dependent way. The imp7‐dependent pathway was specifically competed by excess DNA but not by excess of maltose‐binding protein fused with the classical nuclear localizing signal (NLS) or the M9 peptides. Transport of DNA molecules complexed with poly‐l‐lysine was impaired in intact cells depleted of imp7, and DNA complexes remained localized in the cytoplasm. Poor DNA nuclear import in cells depleted of imp7 directly correlated with lower gene expression levels in these cells compared to controls. Inefficient nuclear import of transfected DNA induced greater upregulation of the interferon pathway, suggesting that rapid DNA nuclear import may prevent uncontrolled activation of the innate immune response. Our results provide evidence that imp7 is a non‐redundant component of an intrinsic pathway in mammalian cells for efficient accumulation of exogenous and endogenous DNA in the nucleus, which may be critical for the exchange of genetic information between mitochondria and nuclear genomes and to control activation of the innate immune response.